Hubungan Antara Penerimaan Diri dengan Kecenderungan Narsistik Perempuan Dewasa Awal Pengguna TikTok - Putri, Dylla Kartika Ayu; Harsono, Yudi Tri (Flourishing Journal, 2024)
The use of social media, especially TikTok, can have negative impacts on its users, such as the emergence of narcissistic tendencies. One factor contributing to the emergence of narcissistic tendencies is the lack of self-acceptance in individuals. Individuals in early adulthood are among the most active users of TikTok. At this stage, individuals explore various things to form their self-integration. One of the ways to explore oneself is through social media. The purpose of this study is to explore the relationship between self-acceptance and narcissistic tendencies among young adult women who use TikTok. The participants in this study were young adult women aged 20 to 40 who were selected using an accidental sampling method. In this study, a total of 156 participants were involved. The results of this study showed that there was a correlation or relationship between self-acceptance and narcissistic tendencies among young adult women who use TikTok (r = -0.269; p < .001). The strength of the relationship is weak and the direction is negative, indicating that the higher the self-acceptance, the lower the narcissistic tendencies. AbstrakPenggunaan media sosial khususnya TikTok dapat memiliki dampak negatif pagi penggunanya, seperti munculnya kecenderungan narsistik. Salah satu faktor dari munculnya kecenderungan narsistik adalah kurangnya penerimaan diri yang dimiliki individu. Individu pada tahap dewasa awal merupakan salah satu pengguna aktif TikTok. Pada tahapan ini, individu mencoba mengeksplorasi berbagai hal untuk membentuk integrasi dirinya. Eksplorasi diri yang dilakukan salah satunya melalui media sosial. Tujuan dari penelitian ini adalah untuk mengeksplorasi hubungan penerimaan diri dengan kecenderungan narsistik perempuan dewasa awal pengguna TikTok. Partisipan dalam penelitian ini adalah perempuan dewasa awal berusia antara 20 hingga 40 tahun yang dipilih dengan menggunakan metode sampling aksidental. Pada penelitian ini didapatkan sebanyak 156 partisipan yang terlibat. Penelitian ini menunjukkan hasil terdapat korelasi atau hubungan penerimaan diri dengan kecenderungan narsistik pada perempuan dewasa awal pengguna TikTok (r = -0,269; p < .001). Tingkat hubungannya lemah dan arahnya negatif meenunjukkan semakin tinggi penerimaan diri maka semakin rendah kecenderungan narsistik.